Endoscopic Mucosal Resection (EMR) for polyps and complex-adenoma lessions of the colon. Recopilation of 15 years of experience (2004-2018) - Yriberry, Simon (2022)
Background: Detection and resection of colonic polypoid sessile and flat lesions, prevents the development of colon cancer. Endoscopic mucosal resection (EMR) has emerged in the 70´s and improved in the 80´s, as an alternative treatment of this lesions and is considered the procedure of choice nowadays, being able to avoid major surgical procedures. Objectives: Evaluation of the results and complications of the technique by endoscopists of a reference center. Review of indications and limitations of the technique. Material and methods: Descriptive, retrospective and observational analysis of patients treated with endoscopic mucosal resection technique at a referral center in Lima, Peru, between January 2004 and December 2018.EMR Technique was used in polypoid lesions greater than 1 cm. The bloc resection and the piecemeal resection technique was used for those lesions up to 3 cm and more. We evaluated complications and results according to the technique as recurrence rate, performing tracking in all cases with endoscopic follow up. Results: 756 lesions and patients (338 women and 298 men) The average age was 61.9 years (37-91 years) and the average lesion size of 20.3 mm (10-50 mm). En bloc or one-piece resection was performed in 78.04 %(590) and piece meal in 21.96%(166) achieving endoscopic and pathological resection. The complication rate in our series was 6.74% and managed endoscopically and with conservative measures and no surgery. Mean follow-up was 18 months (3-24 months) and overall local recurrence rate was 2.49%. After-procedure,additional surgical treatment was performed in 15 cases with pathologic piece report and intramucous adenocarcinoma (IM-ADCA). 13 of 15 local recurrences at 12 months follow up were treated endoscopically and 2 had surgical treatment. Conclusions: Endoscopic mucosal resection (EMR) or Mucosectomy is a technique performed by experts endoscopists and shows low rates of recurrence and complications with suitable material for pathologic examination. It reduces open and laparoscopic surgery.